2011
DOI: 10.1002/lary.21768
|View full text |Cite
|
Sign up to set email alerts
|

The laryngeal mask airway and otorhinolaryngology head and neck surgery

Abstract: The relationship between surgeon and anesthetist is particularly strong in otorhinolaryngology. The impact of airway management on the surgical field and perioperative conditions requires the surgeon to be aware of contemporary tools and techniques available. The LMA has been shown to be safe and efficacious by both the literature and clinical practice. Its use in selected patients should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, some authors have suggested that there is a lower complication rate with laryngeal mask airways 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors have suggested that there is a lower complication rate with laryngeal mask airways 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…LMA usage is not very popular in neck surgery, due to the possibility of displacement after neck extension and surgical manipulations of the trachea, as well as the inconvenience caused by limited access to the airway if adjustments of LMA position are needed during surgery [16]. ETT usage remains the typical practice for major neck surgeries [10]. However, LMA, in combination with a fiberoptic bronchoscope, has been successfully used for intraoperative monitoring of recurrent laryngeal [23–30] and superior laryngeal [31] nerve function.…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal mask airway (LMA) is currently used as an alternative for airway management during thyroidectomy [10–12]. The Protector™ (Teleflex Medical Europe Ltd., Westmeath, Ireland) LMA is a second‐generation supraglottic airway device (SAD) with a built‐in cuff pressure indicator, which ensures filling of the air chamber of the mask with the appropriate volume of air.…”
Section: Introductionmentioning
confidence: 99%
“…The laryngeal mask airway (LMA), which allows the maintenance of upper airway patency without the need for direct visualization of the vocal cords and could avoid potential trauma during the tracheal intubation process, is an alternative to ETT 10 that is gaining popularity in head and neck surgery in the last two decades 11 14 . The potential beneficial impacts of using LMA on minimizing potential damage to the vocal cords and preventing postoperative pharyngolaryngeal symptoms 15 have been supported by the results of previous studies showing a significant reduction in the incidences of postoperative hoarseness and sore throat in patients using LMA compared to those receiving ETT for general anesthesia 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%